Understanding Generation Y Purchase Intentions: Mediating Effects of Uniqueness Needs and Experiential Marketing in MSME Snack Consumption - Syahmardi Yacob; Ade Titi Nifita; Ade Perdana Siregar (Nomico, 2025)
Micro, small, and medium-sized enterprises (MSMEs) play a vital role in Indonesia’s economic resilience, particularly in responding to global health and economic challenges. Among these, the snack food sector in Jambi Province faces increasing pressure to meet the evolving preferences of Generation Y (Gen Y) consumers, who value status, uniqueness, and engaging experiences. This study examines the influence of Gen Y consumer status on purchase intention for MSME snack products, mediated by the need for uniqueness and experiential marketing. Data were collected from 150 MSME owners officially registered with the Jambi BPOM, using stratified random sampling across three regions: Kerinci Regency, Jambi City, and West Tanjung Jabung Regency. The analysis employed SmartPLS 3.0. The findings reveal that Gen Y consumer status significantly influences both the need for uniqueness and experiential marketing. In turn, these mediating variables positively affect purchase intention. Furthermore, the indirect effects of Gen Y status on purchase intention, through both mediators, are stronger than the direct effect. These results underscore the importance for MSMEs to understand and leverage Gen Y consumers’ psychological drivers status orientation, desire for uniqueness, and experience-seeking in designing effective marketing strategies. This study contributes to the consumer behavior literature by highlighting the mediating mechanisms underlying purchase intentions in an emerging market MSME context, and offers practical implications for MSME managers to enhance competitiveness by aligning their offerings with Gen Y’s distinctive preferences.